Maintaining mobility for those fleeing the war in Ukraine: From short-term protection to longer-term perspectives - Steffen Angenendt; Nadine Biehler; Raphael Bossong; David Kipp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2022)
Europe is currently experiencing the largest refugee crisis since World War II. The European Union (EU) has activated the Temporary Protection Directive for the first time. Accordingly, refugees from Ukraine can freely choose where to go, and they have the right to work and receive social benefits in their chosen host country. Even if the number of refugees appears overwhelming, the EU should stick to this approach and build on refugees' social ties and the strong engagement by civil society. A mandatory EU-wide relocation scheme cannot and should not be advanced against the will of many member states and affected refugees. The forced displacement from Ukraine can be managed if self-relocation is actively supported across the entire Schengen zone, if the EU provides sufficient solidarity and financial support for reception and integration measures, and if member states start preparing for sustainable long-term stays from the outset.
Keywords: 320